2022
DOI: 10.1021/acsami.1c25179
|View full text |Cite
|
Sign up to set email alerts
|

Charge Reversal Polypyrrole Nanocomplex-Mediated Gene Delivery and Photothermal Therapy for Effectively Treating Papillary Thyroid Cancer and Inhibiting Lymphatic Metastasis

Abstract: As a traditional treatment for papillary thyroid cancer (PTC), surgical resection of diseased tissues often brings lots of inconveniences to patients, and the tumor recurrence and metastasis are difficult to avoid. Herein, we developed a gene and photothermal combined therapy nanosystem based on a polypyrrole (Ppy)–poly­(ethylene imine)–siILK nanocomplex (PPRILK) to achieve minimally invasive ablation and lymphatic metastasis inhibition in PTC simultaneously. In this system, gelatin-stabilized Ppy mainly acted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…The following probes can all greatly improve the thermal efficacy ( Fig. 3 ) on thyroid tumor cells, achieving precise local thermal ablation of tumors with no significant cytotoxicity observed in animal experiments: Polymeric NPs with bevacizumab and IR825 conjugated on the surface (IR825@B-PPNs) [ 52 ], 131 I-radiolabeled cerebroid polydopamine nano-particles (CPDA- 131 I NPs) [ 53 ], 131 I-labeled BSA-modified CuS nanoparticles ( 131 I-BSA@CuS) [ 54 ], meso-methoxy-substituted DSPE-PEG-2000-coated boron dipyrromethene (B–OMe-NPs) [ 55 ], polypyrrole (Ppy)−poly-(ethylene imine)−siILK nanocomplex (PPR ILK ) [ 56 ], functionalized (epidermal growth factor (EGF), holo-transferrin, or lapatinib) HAOA-coated AuNPs [ 57 ], and photo-triggered Gold nanodots capped mesoporous silica nanoparticles (Au@MSNs) [ 58 ] ( Table 2 ).
Fig.
…”
Section: Phototherapy In Tcmentioning
confidence: 99%
See 1 more Smart Citation
“…The following probes can all greatly improve the thermal efficacy ( Fig. 3 ) on thyroid tumor cells, achieving precise local thermal ablation of tumors with no significant cytotoxicity observed in animal experiments: Polymeric NPs with bevacizumab and IR825 conjugated on the surface (IR825@B-PPNs) [ 52 ], 131 I-radiolabeled cerebroid polydopamine nano-particles (CPDA- 131 I NPs) [ 53 ], 131 I-labeled BSA-modified CuS nanoparticles ( 131 I-BSA@CuS) [ 54 ], meso-methoxy-substituted DSPE-PEG-2000-coated boron dipyrromethene (B–OMe-NPs) [ 55 ], polypyrrole (Ppy)−poly-(ethylene imine)−siILK nanocomplex (PPR ILK ) [ 56 ], functionalized (epidermal growth factor (EGF), holo-transferrin, or lapatinib) HAOA-coated AuNPs [ 57 ], and photo-triggered Gold nanodots capped mesoporous silica nanoparticles (Au@MSNs) [ 58 ] ( Table 2 ).
Fig.
…”
Section: Phototherapy In Tcmentioning
confidence: 99%
“…
Fig. 3 Thermal efficacy of IR825@B-PPNs (A), CPDA- 131 I NPs (B), 131 I-BSA@CuS (C), B–OMe-NPs (D), PPR ILK (E) [ [52] , [53] , [54] , [55] , [56] ]. The temperature fluctuation curves of the indocyanine green (ICG) solution and IR825@B-PPNs after four photothermal heating cycles (A1).
…”
Section: Phototherapy In Tcmentioning
confidence: 99%
“…Gene therapy can improve the efficacy of PTT by inhibiting the expression of specific heat shock proteins and overcoming the resistance of cancer cells to thermal damage ( 280 ). Xu et al ( 281 ) synthesized a polypyrrole-poly(ethyleneimine)-siILK nanocomplex (PPRILK) gene PTT nanosystem based on the siRNA of integrin-linked kinase (ILK). The results of in vivo and in vitro experiments showed that after 808-nm laser irradiation, the tumor growth of the PPRILK treatment group was significantly slower and the damage to normal tissue was minimized compared to the laser and gene therapy groups, indicating that the combination of gene therapy and PTT can effectively ablate tumors and inhibit tumor recurrence.…”
Section: Multimodal Therapy For Tumors Based On Photothermal Nanomate...mentioning
confidence: 99%
“…5,6 Stimuli-responsive materials have been used in the development of drug delivery systems (DDSs) that can control drug release using endogenous stimuli (e.g., enzymes, pH, etc.) 7−9 and exogenous stimuli (e.g., electric fields, 10,11 infrared (IR), 12,13 light, 14,15 magnetism, 16,17 radiation, 18 temperature, 19 and ultrasound, 16 to name a few), 20 with a model DDS allowing control of the location and dosage of the drug, 8,21 Electroactive polymers (EAPs) are a class of stimuliresponsive polymers with a variety of technical and medical applications, with popular nondegradable examples including, but not limited to, polyaniline, polypyrrole, and poly(3,4ethylenedioxythiophene) (PEDOT). 11,22−24 The integration of nondegradable EAPs in medical devices, such as electrodes for sensing/stimulation, offers opportunities to optimize tissue− electrode interactions, such as their mechanical properties (minimizing mechanical mismatch) or the impedance of the electrodes (enhancing the longevity of function).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Stimuli-responsive materials have been used in the development of drug delivery systems (DDSs) that can control drug release using endogenous stimuli (e.g., enzymes, pH, etc. ) and exogenous stimuli (e.g., electric fields, , infrared (IR), , light, , magnetism, , radiation, temperature, and ultrasound, to name a few), with a model DDS allowing control of the location and dosage of the drug, , …”
Section: Introductionmentioning
confidence: 99%